(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Paperboard or paper waste makes up about 26% of the solid waste disposed in landfills and since waste from paper producing factories pollutes the air, water and land; the need to put emphasis on the recycling paper factory products becomes indispensable. From the Architects point of view, affordable housing provision is undoubtedly a vital area that need ultimate intervention in developing cities and suburbs. The aim of this study was to investigate the knowledge and potential of recycled paper as an affordable building material in Ikorodu and its environ. The study adopted a Mixed Method of Research in carrying out the findings. Relevant literature was also reviewed and necessary data were collected through interviews granted to the selected licensed architects within the study area. Structured Questionnaires were administered to architects who are also lecturers in the two schools of architecture in Ikorodu. The selected respondent are either members of the Association of Architectural Educators, Nigerian Institute of Architects or registered with the Architects Registration Council of Nigeria. A total of 65 questionnaires were returned from the 69 administered. Findings revealed that architects have a huge role in building material specifications and that recycled paper exhibits promising attributes, such as lightweight, insulation properties, and thermal performance. It demonstrated satisfactory strength for non-structural applications and showcased potential as an eco-friendly alternative to traditional building materials. Furthermore, the environmental analysis indicated that recycled paper has the potential to contribute to sustainable construction practices, with reduced energy consumption and greenhouse